Analisis Kinerja Keuangan PT. Bank BRI (Persero) Tbk Di Bursa Efek Indonesia (BEI) - Zulkipli Zulkipli; Riman Abimayu; Robby Erviando (Politeknik Negeri Padang, 2024)
The research method used is secondary data analysis from the 2019-2023 period with the financial ratio analysis method used for the first analysis consisting of Loan to Asset Ratio (LAR), Return On Equity (ROE) and Debt to Equity Ratio (DER). The second analysis method uses the development formula to determine the development of PT's net profit. BRI (Persero) Tbk.The results of the analysis carried out concluded, First a). The results of calculating financial ratios, namely the Liquidity ratio, which is represented through the Loan to Assets Ratio (LAR), show that PT. BRI (Persero) Tbk during the 2019-2023 period shows that the average Loan to Assets Ratio (LAR) value is ≤ 75%, namely 60.48%. This means that the financial performance of PT. BRI (Persero) Tbk is relatively healthy from the liquidity aspect. b). The results of calculating financial ratios are the Profitability ratio which is represented through PT's Return On Equity (ROE) ratio. BRI (Persero) Tbk during the 2019-2023 period showed an average Return On Equity (ROE) ratio of 14.48%. PT. BRI (Persero) Tbk is included in Category PK-3, which is classified as an unhealthy bank and is not susceptible to the negative influence of risk factors because the ROE ratio is <17%. c)> The results of the financial ratio calculation, namely the Profitability ratio, which is represented through the Debt to Equity Ratio (DER), show that PT. BRI (Persero) Tbk during the 2019-2023 period showed an average Debt to Equity Ratio (DER) value of 5.43% based on PBI, the health level of commercial banks was ≤ 70% in the healthy category. Second, namely the results of the development of PT's net profit. BRI (Persero) Tbk. experienced a continuous increase from 2019-2023 with an average growth of 25.93%.